The Effect of PPPK Teacher Placement on Teacher Effectiveness and Motivation - Insyarikaduana Insyarikaduana; Bukman Lian; Muhammad Juliansyah Putra (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of Government Contract (PPPK) teacher placement on the effectiveness and motivation of high school teachers in Tulung Selapan District. Employing a quantitative correlational approach, data were collected via questionnaires, observation, and documentation from a sample of 58 PPPK teachers and analyzed using multivariate linear regression and MANOVA. The key result is that placement location has no statistically significant effect on either teacher effectiveness (R²=0.004, p=0.637) or motivation (R²=0.001, p=0.778), as confirmed by MANOVA (Sig.=0.843). The novelty of this research lies in its counterintuitive findings, which challenge the common policy assumption that strategic placement is a primary driver of teacher performance within the Indonesian PPPK system. A major practical implication is that educational authorities should reallocate focus and resources from placement logistics toward strengthening teacher competence, professional development, and supportive school environments. This study contributes evidence-based insight to human resource management in education, suggesting that intrinsic factors and professional capacity are more critical for sustaining high teacher effectiveness and motivation than geographic or institutional assignment.